Perancangan Sistem Aplikasi Registrasi Mitra Online Menggunakan Algoritma Brute Force Pada PT Dayamitra Telekomunikasi (Berbasis Web) - Safhani, Rizca; Akbar, Yuma (Jurnal Vokasi Teknik Informatika, 2021)
This research is motivated by the company's constraints which are currently still doing the Partner Registration process manually, where partners cooperate by sending a hardcopy or physical Company Profile of the Company which makes these documents pile up in our company. Based on this background, it is necessary to create an application for Online Partner Registration Application System Design using a web-based Brute Force Algorithm that aims to help companies The research method used is using qualitative research methods. The design of this application is divided into Data Flow Diagrams, Table Structures, flowcharts and interface design. The development of this application uses codeigniter as a php framework (backend) and uses Black Box and White Box testing. The results of this research, is a website application that will assist in the development of the company and the benefits of this application can be time efficient and facilitate the process of tracing documents.